PENERAPAN MODEL PEMBELAJARA PBL BERBANTUAN APLIKASI CANVA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD INPRES 6/75 MANURUNGE - Firdaus; Kadir, Abd; Hasrawati (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is classroom action research which aims to determine descriptions of teacher activities, student activities, and learning outcomes in implementing the PBL learning model assisted by the Canva application to improve mathematics learning outcomes for class IV students at SD Inpres 6/75 Manurunge. Data collection techniques use observation and tests. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The research results showed that teacher activities in managing learning experienced an increase in the optimal learning process from cycle I to cycle II seen from teacher activities in implementing good learning designs in accordance with the steps of the PBL learning model assisted by the Canva application. Student activity in participating in the learning process has increased from cycle I to cycle II as seen from the results of observations during the learning process using observation sheets. As for student learning outcomes in cycle I, there were 14 out of 20 students who were complete with an average score of 76.25 with a percentage of student learning completeness reaching 70% (fair), while student learning outcomes in cycle II were 17 out of 20 students achieving a complete score with an average score of 87.25 with a percentage of student learning completeness reaching 85% (good). It can be concluded that the PBL learning model assisted by the Canva application can improve student Mathematics learning outcomes.